The significance of teleophthalmology during a pandemic and in general - Kowalik-Jagodzińska, Małgorzata; Turno-Kręcicka, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
The advent of the SARS-CoV2 coronavirus pandemic has significantly affected the quality of medical care delivery. Inefficiencies in the health care system and the fear of spreading the pathogen forced ophthalmologists to start using teleophthalmic methods if they had not done so already. However ophthalmology is an example of a medical specialty that had been benefiting from new technological solutions for many years before the pandemic, which makes it possible to correctly diagnose and treat eye disorders despite limited office visits. This publication aims to present the opportunities of teleophthalmology, which may provide advice for ophthalmologists on how to help pa-tients at a distance without loss of quality. Attention was paid to teleophthalmology tools that may be useful in daily ophthalmic practice both in acute conditions and in the monitoring of patients with chronic conditions, for instance, age-related macular degeneration (AMD) or diabetic retinopathy. This publication presents, among other things, applications that are useful for assessing visual acuity, tonometers that can be used for self-measurement of intraocular pressure without leaving home. Moreover, this publication assesses the quality of photos taken with a smartphone for the evaluation of the anterior and posterior segments of the eye.